Epidemiology and molecular biology of head and neck cancer - Jou, Adriana; Heß, Jochen (Oncology research and treatment, 2017)
Head and neck cancer is a common and aggressive malignancy with a high morbidity and mortality profile. Although the large majority of cases resemble head and neck squamous cell carcinoma (HNSCC), the current classification based on anatomic site and tumor stage fails to capture the high level of biologic heterogeneity, and appropriate clinical management remains a major challenge. Hence, a better understanding of the molecular biology of HNSCC is urgently needed to support biomarker development and personalized care for patients. This review focuses on recent findings based on integrative genomics analysis and multi-scale modeling approaches and how they are beginning to provide more sophisticated clues as to the biological and clinical diversity of HNSCC.